Increase of electricity price and energy efficiency: analysis using the macroeconomic interindustry model of Taiwan. Issue 3 (3rd July 2017) - Su, Yu-Wen; Yang, Hao-Yen; Lin, Chih-Hsun
ABSTRACT: From 2012 to 2013, the price of electricity in Taiwan increased by 19.78%. This large increase forced producers to invest in improving electricity efficiency. In this paper, the macroeconomic interindustry model of Taiwan (MEIT) is developed to study the economic effects of high electricity prices and consequential improvement in energy efficiency. MEIT describes the structure of 47 industries, from both real and price-income approaches. To resolve inconsistent data, RAS is employed. A technical model is also integrated to consider technical feasibility, which offsets the usual shortcomings of technological analysis in an economic model. The iron and steel industry is taken as a case study. Estimated results indicate that higher electricity prices negatively affect Taiwan's economy. However, improving energy efficiency can reduce some of this effect.